STRATEGIES AND CHALLENGES OF PUBLIC RELATIONS MANAGEMENT IN FACING THE ERA OF SOCIETY 5.0 - Eka Diana; Khofifah, Khofifah (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to analyze improving public relations strategies in facing challenges in the era of society 5.0. This research uses qualitative descriptive analysis with a case study approach. The research was conducted at Madrasah Ibtidaiyah Islamiyah Kertosono Gading Probolinggo. Data collection techniques were carried out using interviews, observation and documentation. The results of this research show that community involvement in carrying out school activities is carried out through routine activities and incidental activities. With several social media accounts, it makes it very easy for public relations to provide various information related to madrasas and also makes it easier for the public to access information. The media used include: WhatsApp, YouTube, Facebook, Instagram and website accounts. Not only using media, the strategies used in MI Islamiyah are planning, implementation, results and then continuous improvement.